LIVED SPACES IN LATE ANTIQUITY - Machado, Carlos; Munnery, Rowan; Sweetman, Rebecca J. ([S.l.] : ROUTLEDGE, 2024)
This volume considers lived space as a scholarly approach to the past, showing how spatial approaches can present innovative views of the world of Late Antiquity, integrating social, economic and cultural developments and putting centre stage this fundamental dimension of social life. Bringing together an international group of scholars working on areas as diverse as Britain, the Iberian Peninsula, Jordan and the Horn of Africa, this book includes burgeoning fields of study such as lived spaces in the context of ships and seafaring during this period. Chapters investigate the history, function and use of different spaces in their own right and identify the social and historical logic presiding over continuity and/or change. They also explore the fluidity of lived space in both its physical and conceptual dimensions, analysing issues like agency and intentionality as well as meaning and social relations. Space is the fundamental dimension of social life, the arena where it unfolds and the stage where social values and hierarchies are represented; analysis of space allows us to understand history through different means of shaping, occupying and controlling space. Considering Late Antiquity through a spatial perspective offers a complex and stimulating picture of this pivotal period, and this volume provides avenues for the development of further research and discussion in this area. Lived Spaces in Late Antiquity is a fascinating resource for students and scholars interested in space and spatiality in the late antique world, as well as archaeology, classical studies and late antique studies more generally.
Keywords: Space (Architecture) -- History; HISTORY / Ancient / General